Crafting the Past: Theory and Practice of Museums - Katherine Ambry Linhein Muller (EXARC Journal)
How do we know something is real? We say something exists when it is tangible and we can touch it; it is factual when we can compare it to other known variables, and historic when it fulfils our expectation of the past. There are objects and activities that blur these categories and cause people to accept alternative histories. A museum is one such example. The buildings are constructed for displays, the people are only performers and the sounds and smells are fabricated, but the experiences, though they vary from person to person, are real. At museums the public and the interpreters interact in a shared space but not a shared mindset. By borrowing from Mark Leone’s critical theory it is possible to examine the dissonance between the museum’s production of history and the public’s perception.